PENGARUH STRATEGI POSITIONING DAN HUMAN CAPITAL TERHADAP KINERJA PERUSAHAAN PADA PTPN VIII BUNISARI LENDRA - Zenal Mutaqin; Ade Burhanudin (Gapenas Publisher, 2021)
Service companies can invest in executing positioning and human capital strategies so that employees can have the ability to deal with potential variations in customer demand, according to the company's positioning strategy. Therefore, service companies that have a matching strategy for positioning and human capital will get a greater increase in performance. So it can be concluded that the positioning strategy and human capital have a significant effect on company performance. efforts to improve company performance are by measuring the level of the positioning strategy used by the company, namely: Customer Co-Production, namely implementing a different strategy from competing companies; Customer Contact, namely identifying customer desires by way of interaction; and Service Customization, where companies must be able to change their products according to specific consumer needs